SMALL BUSINESS AND PRIVATE ENTREPRENEURSHIP: DRIVING FORCES IN UZBEKISTAN'S ECONOMY (American Journal of Business Management, Economics and Banking, 2023)
The article delves into the pivotal role played by small businesses and private entrepreneurship within the Republic's economy. It meticulously examines the distinctions between entrepreneurship and business, drawing from comprehensive analyses of these concepts alongside insights from both foreign and Uzbek economists. Moreover, it synthesizes findings from scholarly research in this realm while intertwining personal perspectives. A critical aspect involves scrutinizing the attained outcomes within the national economy concerning entrepreneurship and business, leveraging statistical data to draw informed conclusions. The article scrutinizes the proportions of small business and private entrepreneurship across diverse sectors, employing analytical methodologies. Utilizing collected statistical data, the article constructs an econometric model, facilitating the prediction of the future share of small business and private entrepreneurship within the GDP for forthcoming years. This empirical approach underpins the article's exploration, providing a predictive framework for understanding the trajectory of these sectors within the Republic's economic landscape.